Young adult cancer caregivers' use of social media for social support. Issue 7 (19th May 2020) - Warner, Echo L.; Kirchhoff, Anne C.; Ellington, Lee; Waters, Austin R.; Sun, Ye; Wilson, Andrew; Cloyes, Kristin G.
Abstract: Objective: To describe how young adult cancer caregivers (YACC) use social media for social support during a cancer experience. Methods: Eligible YACC were 18 to 39 years, used Facebook and/or Instagram at least once per week, and cared for an adult cancer patient diagnosed 6 months to 5 years prior (N = 34). Recruitment of a cross‐sectional sample occurred through oncology clinics in Utah and online advertising by caregiving and cancer organizations from September 2017 to June 2018. Semi‐structured telephone interviews were recorded, transcribed, iteratively coded, and qualitatively analyzed, yielding four categories concerning how YACC use social media. Results: Caregivers were most commonly spouses aged 29 years on average (range 21‐38); cancer patients were 37 years (range 19‐76). Analysis yielded four distinct yet related categories: Category 1: Posting about cancer on social media often begins as a strategy for YACC to efficiently provide updates about the cancer patient. Category 2: Caregivers who actively post on social media experience a variety of different functional social supports to which they otherwise would not have access. Category 3: Posting about cancer online presents an opportunity for negative consequences. Category 4: Potential for negative consequences influences how some caregivers use social media. Conclusions: Supportive services, including social media‐based supports, are needed for YACC in formats that are convenient for them as they balance their caretaking duties with their daily lives.